Le corps-écriture dans l’œuvre de Franz Kafka et du premier Henri Michaux - Isabelle Benguigui (Recherches Germaniques)
In his diaries as well as in his narratives, Franz Kafka readily likened the human body to the organic life of his texts. Poet Henri Michaux similarly built his work on the indestructible link between flesh and writing to make the difficult representation of his singular being possible. Here, the self can be embodied only in “body-writing”, in which the whole man is identified with his artistic expression. It remains to be seen if this physical and verbal alliance that is Kafka’s legacy to Michaux carries the same power and the same intention in both worlds. This study seeks to define how contemporary French poetry has appropriated Kafka’s literary legacy, as Michaux himself claimed to reconnect the ills of body and soul with the resources of poetic expression.